Hydroelectric power generation in an Alpine basin: future water-energy scenarios in a run-of-the-river plant. (August 2016) - Bongio, Marco; Avanzi, Francesco; De Michele, Carlo
Highlights: We focus on scenarios of hydroelectric generation in an Alpine basin; A hydrological model and a conversion to energy are considered; A set of future climate scenarios are built from observed climate; Two IPCC-like scenarios and two glacier inventories are considered; Hydroelectric generation is predicted to decrease at the plant; Abstract: We investigate scenarios of hydroelectric power generation for an Alpine run-of-the-river plant in 2050. To this end, we include a conversion from streamflow to energy in a hydrological model of the basin, and we introduce a set of benchmark climate scenarios to evaluate expected future production. These are a "future-like-present" scenario assuming future precipitation and temperature inputs to be statistically equivalent to those observed during the recent past at the same location, a "warmer-future" scenario, which considers an additional increase in temperature, and a "liquid-only" scenario where only liquid precipitation is admitted. In addition, two IPCC-like climatic scenarios (RCP 4.5 and RCP 8.5) are considered. Uncertainty in glaciers' volume is accounted by initializing the hydrological model with two different inventories of glaciers. Ensemble results reveal that 1) an average decrease between -40% and -19% of hydroelectric power generation in 2050 is predicted at the plant considered (with respect to present condition); 2) an average decrease between -20% and -38% of cumulative incoming streamflow volume at the plant is also predicted, again with respect to present condition; 3) these effects are associated with a strong average decrease of the volume of glaciers (between -76% and -96%, depending on the initial value considered). However, Monte Carlo simulations show that results are also prone to high uncertainties. Implications of these results for run-of-the-river plants are discussed.